Nutrient regulation of signaling and transcription - Hart, Gerald W. (The Journal of biological chemistry, 2019)
In the early 1980s, while using purified glycosyltransferases to probe glycan structures on surfaces of living cells in the murine immune system, we discovered a novel form of serine/threonine protein glycosylation (O-linked β-GlcNAc; O-GlcNAc) that occurs on thousands of proteins within the nucleus, cytoplasm, and mitochondria. Prior to this discovery, it was dogma that protein glycosylation was restricted to the luminal compartments of the secretory pathway and on extracellular domains of membrane and secretory proteins. Work in the last 3 decades from several laboratories has shown that O-GlcNAc cycling serves as a nutrient sensor to regulate signaling, transcription, mitochondrial activity, and cytoskeletal functions. O-GlcNAc also has extensive cross-talk with phosphorylation, not only at the same or proximal sites on polypeptides, but also by regulating each other’s enzymes that catalyze cycling of the modifications. O-GlcNAc is generally not elongated or modified. It cycles on and off polypeptides in a time scale similar to phosphorylation, and both the enzyme that adds O-GlcNAc, the O-GlcNAc transferase (OGT), and the enzyme that removes O-GlcNAc, O-GlcNAcase (OGA), are highly conserved from C. elegans to humans. Both O-GlcNAc cycling enzymes are essential in mammals and plants. Due to O-GlcNAc’s fundamental roles as a nutrient and stress sensor, it plays an important role in the etiologies of chronic diseases of aging, including diabetes, cancer, and neurodegenerative disease. This review will present an overview of our current understanding of O-GlcNAc’s regulation, functions, and roles in chronic diseases of aging.